2020
DOI: 10.3847/1538-4357/abc699
|View full text |Cite
|
Sign up to set email alerts
|

Noninteracting Black Hole Binaries with Gaia and LAMOST

Abstract: Until recently, black holes (BHs) could be discovered only through accretion from other stars in X-ray binaries, or in merging double compact objects. Improvements in astrometric and spectroscopic measurements have made it possible to detect BHs also in noninteracting BH binaries (nBHBs) through a precise analysis of the companion’s motion. In this study, using an updated version of the StarTrack binary-star population modeling code and a detailed model of the Milky Way (MW) galaxy, we calculate the expected n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 133 publications
2
25
0
Order By: Relevance
“…Whether there is the mass gap or not can shed light on supernova mechanisms for the formation of NSs and BHs. Although Gaia astrometry was already claimed to be able to discover invisible BHs with optical companions (e.g., Gould & Salim 2002;Mashian & Loeb 2017;Breivik et al 2017;Yalinewich et al 2018;Yamaguchi et al 2018;Breivik et al 2019;Shao & Li 2019;Andrews et al 2019;Wiktorowicz et al 2020), merging BH-CS binaries that appear as GW sources are alternatively potential objects to test the mass gap and relevant supernova mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Whether there is the mass gap or not can shed light on supernova mechanisms for the formation of NSs and BHs. Although Gaia astrometry was already claimed to be able to discover invisible BHs with optical companions (e.g., Gould & Salim 2002;Mashian & Loeb 2017;Breivik et al 2017;Yalinewich et al 2018;Yamaguchi et al 2018;Breivik et al 2019;Shao & Li 2019;Andrews et al 2019;Wiktorowicz et al 2020), merging BH-CS binaries that appear as GW sources are alternatively potential objects to test the mass gap and relevant supernova mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that observations of repeating SL flares are a promising way of detecting non-interacting compact object binaries. Using the comprehensive model of the Milky Way galaxy developed in Wiktorowicz et al (2020) and the database of BHs in stellar populations (Wiktorowicz et al 2019) extended for systems in which the compact object is a NS, we have calculated realistic predictions for three ongoing or planned large-area optical surveys: ZTF GPS, TESS, and the Vera Rubin-LSST. Our results indicate that such current or future optical surveys may have the ability to detect hundreds to thousands of SL binary systems.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the stellar mass distribution in the Galaxy, we use the Milky Way model of Robin et al (2003), modified as described in Wiktorowicz et al (2020). Following the procedure introduced in Wiktorowicz et al (2020), which improves on the traditional Monte Carlo-based sampling methods, we calculated the fraction of the Galactic mass within a distance 𝑑, observable from the Earth for the 1 https://universeathome.pl/universe/bhdb.php instruments under consideration (Figure 2). To calculate bolometrically corrected absolute magnitude (𝑚 abs ) we use the YBC database (Chen et al 2019, see also Sec 2.4).…”
Section: Observational Predictionsmentioning
confidence: 99%
See 2 more Smart Citations